Revised market segmentation for spring wheat—achieving alignment between ICARDA and CIMMYT - Mbugua-Gitonga, Agnes; Wuletaw, Tadesse; Velu, Govindan; Donovan, Jason (CGIAR Initiative on Market Intelligence, 2024)
The article discusses efforts to align market segmentation for spring wheat between ICARDA and CIMMYT within the CGIAR initiative. Initially, both centers presented separate market segments for the same regions, causing duplication. To address this, the initiative has worked toward a unified "crop view" for better crop prioritization based on regional market needs. This approach resolves duplication, ensures alignment of target product profiles, and clarifies which market segments are addressed or overlooked. The case of spring wheat illustrates how this alignment improves focus on farmer and consumer needs, rather than just breeding pipelines.